Enabling Reduced Simpoint Size Through LiveCache and Detail Warmup - Jose Renau; Fangping Liu; Hongzhang Shan; Sang Wook Stephen Do (BenchCouncil Transactions on Benchmarks, Standards and Evaluations, 2022)
Simpoint technology (Sherwood et al., 2002) has been widely used by modern micro-architecture research community to significantly speedup the simulation time. However, the typical Simpoint size remains to be tens to hundreds of million instructions. At such sizes, the cycle-accurate simulators still need to run tens of hours or even days to finish the simulation, depending on the architecture complexity and workload characteristics. In this paper, we developed a new simulation framework by integrating LiveCache and Detail-warmups with Dromajo ( https://chipyard.readthedocs.io/en/latest/Tools/Dromajo.html) and Kabylkas et al. (2005), enabling us to use much smaller Simpoint size (2 million instructions) without loss of accuracy. Our evaluation results showed that the average simulation time can be accelerated by 9.56 times over 50M size and most of the workload simulations can be finished in tens of minutes instead of hours.